Matrine-induced nephrotoxicity via GSK-3β/nrf2-mediated mitochondria-dependent apoptosis. (1st June 2023) - Wang, Tianyang; Zhang, Jian; Wei, Haokai; Wang, Xi; Xie, Minjuan; Jiang, Yinjie; Zhou, Jie
Abstract: Introduction: Matrine (MT), an ingredient extracted from the Chinese herb Sophora flavescens, can result in nephrotoxicity because of long-term exposure. However, the underlying mechanism by which MT leads to kidney injury remains unclear. This study aimed to investigate the roles of oxidative stress and mitochondria in MT-induced kidney toxicity both in vitro and in vivo . Methods: Mice were exposed to MT for 20 days, and NRK-52E cells were exposed to MT with or without LiCl (a GSK-3β inhibitor), tert-Butylhydroquinone (t-BHQ, an Nrf2 activator), or small interfering RNA. Results: The results showed that MT caused nephrotoxicity accompanied by an increase in reactive oxygen species (ROS) accumulation and mitochondrial dysfunction. Meanwhile, MT significantly upregulated glycogen synthase kinase-3β (GSK-3β) activity, released cytochrome c (Cyt C) and cleaved caspase-3, decreased the activity of nuclear factor-erythroid 2-related Factor 2 (Nrf2), and reduced the expression of heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 (NQO-1), which led to the inactivation of antioxidant enzymes and the activation of apoptosis. In addition, GSK-3β inhibition by LiCl or small interfering RNA pretreatment or Nrf2 activation by t-BHQ pretreatment attenuated the toxic effects of MT in NRK-52E cells. Conclusions: Taken together, these results revealed that MT-induced apoptosis triggered kidney toxicity and that GSK-3β or Nrf2 might serve as a promising nephroprotective target for MT-induced kidney injury. Highlights: Matrine has potential toxicity to the kidney. The nephrotoxicity effects of matrine involve GSK-3β/Nrf2-mediated oxidative stress. The nephrotoxicity effects of matrine involve GSK-3β/Nrf2-mediated apoptosis. GSK-3β may be a nephroprotective target for treating matrine-induced nephrotoxicity. Nrf2 may be a nephroprotective target for treating matrine-induced nephrotoxicity.